Controls on Lunar Basaltic Volcanic Eruption Structure and Morphology: Gas Release Patterns in Sequential Eruption Phases. Issue 12 (20th June 2018) - Wilson, L.; Head, J. W.
Abstract: Assessment of mare basalt gas release patterns during individual eruptions provides the basis for predicting the effect of vesiculation processes on the structure and morphology of associated features. We subdivide typical lunar eruptions into four phases: Phase 1, dike penetrates to the surface, transient gas release phase; Phase 2, dike base still rising, high‐flux hawaiian eruptive phase; Phase 3, dike equilibration, lower flux hawaiian to strombolian transition phase; and Phase 4, dike closing, strombolian vesicular flow phase. We show how these four phases of mare basalt volatile release, together with total dike volumes, initial magma volatile content, vent configuration, and magma discharge rate, can help relate the wide range of apparently disparate lunar volcanic features (pyroclastic mantles, small shield volcanoes, compound flow fields, sinuous rilles, long lava flows, pyroclastic cones, summit pit craters, irregular mare patches, and ring moat dome structures) to a common set of eruption processes. Plain Language Summary: Since the early days of close‐up orbital observations of the lunar surface in the 1960s, a large number of lunar volcanic landforms have been identified and cataloged, including explosive volcanic mantles, small shield‐shaped volcanoes, compound flow fields, meandering sinuous rille channels, long lava flows, volcanic cones, volcanic pit craters, and very unusual and enigmatic features called irregular mare patches and ring moat dome structures. Unknown is how all of these different features form and how they might fit together in different stages or phases of lunar volcanic eruptions. Interpretation is complicated by the effects of low lunar gravity and lack of an atmosphere, both encouraging very different patterns of gas release during lunar volcanic eruptions. We examine the nature of the rise, eruption, and gas release of lavas from the lunar interior and show how four phases of mare basalt eruptions can help relate the wide range of apparently disparate lunar volcanic features to a common set of eruption processes. This is important because it links the observed geologic record to specific physical volcanology predictions that can be further tested with future exploration and analysis. Key Points: Relationships between a diverse array of lunar mare effusive and explosive volcanic deposits and landforms have previously been poorly understood Four phases in the generation, ascent, and eruption of magma and gas release patterns are identified and characterized Specific effusive, explosive volcanic deposits, and landforms are linked to these four phases in lunar mare basalt eruptions in a predictive and integrated manner